THE GENETIC POTENTIAL OF BARLEY IN SIBERIA AND ITS IMPORTANCE FOR BREEDING - N. A. Surin (Vavilovskij Žurnal Genetiki i Selekcii, 2015)
The results of breeding of hulled and naked Siberian spring barley varieties for various purposes, characterized by early ripening, high productivity, large seed sets, and tolerance of adverse environmental factors, are reviewed.